Determination of the Reliability Interval of Outdoor Channel Model in 802.15.4/Zigbee Networks - Vega-Viveros, R; Kaschel-Carcamo, H; Quezada-Cartes, G; Sanchez-Y Bernal, L (National Institute for R and D in Informatics, 2011)
Within the framework of the implementation of a wireless network of nodes under the IEEE802.15.4/Zigbee standard, the values obtained from experimental measurements of power as a function of distance between nodes in free space are analyzed. A propagation loss model is proposed and a statistical analysis is made to determine the reliability of the prediction of the distance between nodes as a function of the power measured at the receiver. This analysis confirms that the predictions obtained from the proposed model and from widely used models, are not appropriate for determining, with a high degree of certainty, the distance between transmitter and receiver due to the variability of the data.